A High Step-Up DC-DC Converter With Switched-Capacitor and Coupled-Inductor Techniques - Zhang, Min; Wei, Zhengyi; Zhou, Mingzhu; Wang, Fenglian; Cao, Yichang; Quan, Limin (IEEE journal of emerging and selected topics in industrial electronics (Print), 2022)
This article proposes a high step-up dc-dc converter with single switch, which combines a multiplier voltage cell, two winding coupled inductor, and switched capacitor. The converter attained high voltage gain by the boost cell consisting of two winding coupled inductor and switched capacitor. A passive clamp circuit consisting of diode and capacitor can reduce the voltage spike of switch S and recover leakage inductance energy. Therefore, the power switch with low on -state resistance can be used, which will reduce the conduction losses of the switch S . The main properties of the suggested converter are high voltage gain with low turn ratio n at reasonable duty cycle D , and high efficiency. The operation modes and steady-state analysis are presented. Moreover, the stress of the components, theoretical efficiency analysis, and comparison with other dc-dc converters are analyzed and presented, respectively. Finally, a 200 W prototype construct in the laboratory based on the design guidelines verifies the validity of the suggested converter.